Low medium cost housing in Malaysia: Issues and challenges - Shuid, Syafiee (2004)
Housing provision for all in any country is very crucial in order to ensure social- economic stability and to promote national development. Therefore the Malaysian government under its 5 year National Plan has introduced the low, medium and high cost housing categories. Under the Seventh Malaysia Plan (1996-2000) the government for the first time introduced the Low Medium Cost Housing category (previously it was classified together with medium cost housing category) due to the ever increasing demand for housing in this category.This is to ensure that the middle low income group with salary ranging from RM1,501(USD395) to RM2,500 (USD658) per month able to own a house. However, provision of low medium cost housing or house costing from RM42,001 (USD11,503) to RM60,000 (USD15,789) per unit projected under Seventh Malaysia Plan is very disappointed with only 20.7% or 72,582 unit completed from 350,000 unit targeted nationwide.The need to examine the cause of the problems associated with the implementation oflow medium cost housing to ensure the success of future housing policy in Malaysia. For this purpose, the study will look into the implementation of low medium cost housing policy with special reference to Kuala Lumpur as case study.